Can Serum Pancreatic Amylase and Lipase Levels Be Used as Diagnostic Markers to Distinguish Between Patients With Mucinous Cystic Lesions of the Pancreas, Chronic Pancreatitis, and Pancreatic Ductal Adenocarcinoma?. Issue 9 (October 2016) - Pezzilli, Raffaele; Melzi d'Eril, Gianvico; Barassi, Alessandra
Abstract : Objective: This study aimed to assess the presence of pancreatic hyperenzymemia in patients with pancreatic cystic lesions as compared to other chronic diseases of the pancreas. Methods: Ninety-one patients were studied: 32 had mucinous cystic lesions, 35 had chronic pancreatitis (CP), and 24 had pancreatic ductal adenocarcinoma (PDAC). Surgery was carried out in 10 of the 32 patients with mucinous cystic lesion (7 of them had severe dysplasia), in 5 patients with CP, and in 9 patients with PDAC. Results: Abnormally high serum pancreatic isoamylase activity was present in 11 (34.4%) patients with mucinous cystic lesions, in 14 (40.0%) patients with CP, and none in patients with PDAC ( P = 0.002); whereas serum lipase activity was abnormally high in 8 (25.0%) patients with mucinous cystic lesion, in 17 (48.6%) patients with CP, and in 3 (12.5%) patients with PDAC ( P = 0.009). In 7 patients with mucinous cystic lesions and histologically confirmed severe dysplasia, abnormally high levels of both serum pancreatic amylase and lipase were present in 3 (42.9%) patients. Conclusions: High serum concentrations of pancreatic amylase and lipase were found in no more than half of the patients with mucinous cystic lesions. High levels of pancreatic enzymes were not associated with a greater risk of malignancy.